The manga guide to regression analysis - Takahashi, Shin.; Inoue, Iroha; Trend-pro Co. (2016)
"A guide to regression analysis that combines Japanese-style manga cartoons with educational content. Concepts include matrix equations, inverse functions, logarithms, and differentials. Also covers single, multiple, and binomial logistic regression analysis, hypothesis tests, analysis of variance, F and Chi-squared distributions, and confidence intervals"--
Includes index.
Keywords: Regression analysis; Graphic novels